A demographic portrait of urban open field cultivators in Gweru, Zimbabwe - Batanai, Sammie, L.; Gwazane, Munyaradzi; Nyamutowa, Charles (International Journal of Scientific Research, 2016)
The formulation of effective policies and regulations to regulate urban agriculture in Zimbabwe has to be informed by research. This study sought to provide kernel demographic information to be later used in the formulation of models to investigate the impacts of proposed legislation on urban open field cultivation. A questionnaire driven survey was used to obtain data from 40 cultivators residing in Gweru, Zimbabwe. It was discovered that 58% of field owners were men, with 76% of all field owners being between 25 - 65 years. Children were found to contribute 35% of the labour. The majority of cultivators were formally educated; 15% had tertiary/university education, 5% ‘A’-level, 48% ‘O’-level and 27% primary level education. The study concluded that open field cultivation is a family practice engaged in by all social classes and thus recommended that urban agriculture be legitimized as it is an integral part of Zimbabwean urban life